Co-designing a Program to Improve Post-stroke Sexual Rehabilitation: The Promise of Innovative Methods - Auger, Louis-Pierre; Allegue, Dorra Rakia; Morales, Ernesto; Thomas, Aliki; Filiatrault, Johanne; Vachon, Brigitte; Rochette, Annie (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Most people who sustain a stroke are likely to experience sexual difficulties during their recovery. However, few people get the opportunity to address sexuality during their rehabilitation because of factors related to the organization (e.g., culture), managers (e.g., lack of resources), clinicians (e.g.,perceived lack of knowledge, skills, and comfort), and clients (e.g., taboo). A multifactorial program tailored to stakeholders’ needs with various complementary interventions is needed to lead to a change of practice in post-stroke sexual rehabilitation. Objective: To co-design with stakeholders (i.e., people with stroke, clinicians, managers and researchers) a theory-driven multifactorial program to improve post-stroke sexual rehabilitation services. Methods: This qualitative study will be conducted in four steps using an Intervention Mapping approach and a co-design methodology divided into four phases: 1) exploration; 2) co-design; 3) validation; and 4) development. One person with stroke, clinicians and managers from five distinct stroke rehabilitation centers in the province of Quebec (Canada), and researchers will be recruited to either participate in an advisory committee or working groups throughout the study. A combination of contributions from three different types of groups (advisory group, Lego® groups, work groups) will be used for data collection. Qualitative data analysis will first be realized by two independent reviewers using the Theoretical Domains Framework, and preliminary results of analysis will be validated with the advisory and working groups. Conclusion: This study will lead to the co-design of the first theory-driven program intended to optimize post-stroke sexual rehabilitation services.